Three Hundred Years of Crisis in Economic Dictionaries and Encyclopaedias - Tarp, Sven (HERMES - Journal of Language and Communication in Business, 2012)
This article discusses the book Crises and Cycles in Economic Dictionaries and Encyclopaedias from a lexicographical point of view. Although the book is mainly written to people interested in the history of economics and the evolution of the two concepts mentioned in the title, its fresh approach places it directly, although incidentally, in the on-going discussion on the academic character of lexicography. After briefly presenting the main content of the book, the article discusses the relation between economics and lexicography from various angles. Finally, it points to some elements where the book may contribute to the enrichment of lexicographical theory.